Warm Water Foot Soak Therapy To Reduce Anxiety In Trimester III Pregnant Women At Sikumana Health Centre - Mandala, Alin Dhayu; Kapitan, Meiyeriance; Kleden, Simon Sani (Sean Institute, 2024)
During the III trimester, most pregnant women experience anxiety. One of the therapies that can be done to reduce anxiety in third trimester pregnant women is warm water foot bath therapy. The purpose of this study was to determine warm water foot bath therapy to reduce anxiety in third trimester pregnant women at Sikumana Health Center. This study used a qualitative approach with a type of case study research with a descriptive case study research design. The subjects of this study were two patients of third trimester pregnant women who were determined based on the inclusion and exclusion criteria. The anxiety instrument used was the Depression Anxiety Stress Scale (DASS) questionnaire. The results obtained, before the warm water foot soak therapy, Mrs. M's anxiety level was very severe anxiety (Score 30), and Mrs. A's anxiety level was severe anxiety (Score 19). After performing warm water foot bath therapy for 3 consecutive days with a duration of 10-20 minutes every day, the results showed a decrease in anxiety levels, in Mrs. M to a severe anxiety level (Value 19), and in Mrs. A to a moderate anxiety level (Value 14). The conclusion of this study, warm water foot soak therapy can reduce anxiety in third trimester pregnant women. It is expected that patients and families can apply warm water footbath therapy to reduce anxiety in third trimester pregnant women.